ANALISIS QUALITY WORK OF LIFE DALAM MENINGKATKAN KINERJA KARYAWAN PADA PT. BANK BTPN TBK. KANTOR CABANG KENDARI - Made Sugamayasa; Pasrun; Muh. Nur (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2024)
The objective of this study is to identify and analyze the impact of Quality Work of Life on enhancing employee performance at PT. Bank BTPN Tbk, Kendari Branch Office. The total number of employees at PT. Bank BTPN Tbk, Kendari Branch Office is 17, with the branch manager serving as the key informant. The data analysis method is aligned with the research objectives, aiming to depict and analyze a phenomenon by describing the research focus related to the investigated problem. This research utilizes a qualitative descriptive analysis method in accordance with the perspective of Miles and Huberman. The findings indicate that Quality Work of Life can improve the performance of employees at PT. Bank BTPN Tbk, Kendari Branch Office in terms of work quality, work quantity, punctuality, effectiveness, and autonomy. Consequently, employee participation, conflict resolution, communication, work health, work safety, job security, adequate compensation, pride, and career development at PT. Bank BTPN Tbk, Kendari Branch Office are well implemented.